Outbound logistics resilience considering customer participation level: A case study of Thailand’s sugar factory - Watanabe, Woramol C.; Wichaisri, Sooksiri; Patitad, Patchanee (Engineering and Applied Science Research, 2023)
The sugar industry plays an important role in Thailand’s economy. Due to current disruptions, the sugar supply chain is facing a drop in demand and a labour shortage. This has forced the chain to adapt to get through this crisis. To do so, the supply chain resilience concept becomes of the utmost importance and can ensure a prompt and efficient process. Especially outbound logistics are of concern, being time- and labour-consuming due to the heavy weight and large volume nature of sugar. This means the chain is fragile and lacks resilience. To enhance the resilience, process improvement initiatives and collaboration with customers are now in focus to minimise the processing time and labour. Analysis of the relationship between the level of customer participation and improvement results is also proposed to provide valuable insights for decision-makers in their investment planning. In this paper, waste that impacts the processing time is eliminated after the analysis reveals that the most time-consuming steps are preparing the product based on the order and arranging the products in the truck, primarily involving movement of the sugar. The solutions proposed to improve these processes include the implementation of push-pull forklift technology and a booking system, resulting in a 20.25% reduction in the overall processing time. By fully leveraging the booking system and optimising the forklift system, the overall processing time can be further reduced by 39.29%. To achieve the optimal performance, it is recommended to utilise the booking system to its maximum capacity, ideally reaching 100% utilisation but at least exceeding 50%.